2018
DOI: 10.3390/molecules23112823
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Expression Analysis in WM164 Melanoma Cells Revealed That β-β-Dimethylacrylshikonin Leads to ROS Generation, Loss of Mitochondrial Membrane Potential, and Autophagy Induction

Abstract: Skin cancer is currently diagnosed as one in every three cancers. Melanoma, the most aggressive form of skin cancer, is responsible for 79% of skin cancer deaths and the incidence is rising faster than in any other solid tumor type. Previously, we have demonstrated that dimethylacrylshikonin (DMAS), isolated from the roots of Onosma paniculata (Boraginaceae), exhibited the lowest IC50 values against different tumor types out of several isolated shikonin derivatives. DMAS was especially cytotoxic towards melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Of relevance to melanoma, DO-SHI has been found to induce apoptosis in B16-F10, 15 and β,β-SHI is reported to trigger apoptosis in the human melanoma WM164 cell line. 1 Based on the limited understanding of DO-SHI and β,β-SHI and the promising data from our recent study, we believe that SHI, DO-SHI, and β,β-SHI offer potential novel interventions for melanoma. Data from the Alamar blue assay indicate that SHI, DO-SHI, and β,β-SHI inhibit A375, B16-F0, and B16-F10 cell viability in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Of relevance to melanoma, DO-SHI has been found to induce apoptosis in B16-F10, 15 and β,β-SHI is reported to trigger apoptosis in the human melanoma WM164 cell line. 1 Based on the limited understanding of DO-SHI and β,β-SHI and the promising data from our recent study, we believe that SHI, DO-SHI, and β,β-SHI offer potential novel interventions for melanoma. Data from the Alamar blue assay indicate that SHI, DO-SHI, and β,β-SHI inhibit A375, B16-F0, and B16-F10 cell viability in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…Despite accounting for about 4% of all skin cancer cases, invasive melanoma contributes to more than 79% of all skin cancer deaths. 1 The cost of treating skin cancer differs according to the stage of the disease as well as the country in which the treatment is received. 2 The average cost of treating melanoma is estimated at USD 3.3 billion annually in the United States.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, natto freeze-drying extract and natto water extract, isolated from natto, soybeans fermented by Bacillus subtilis natto , were considered to play a critical role in melanoma cell death through ROS adjustment, autophagy regulation and apoptosis promotion [ 129 ]. In addition, dimethylacrylshikonin, isolated from the roots of Onosma paniculata (Boraginaceae), induced apoptosis, autophagy, ROS generation and loss of mitochondrial membrane potential in WM164 cell line [ 130 ].…”
Section: Melanoma Cell Death and Survival: Simultaneous Regulation Of Oxidative Stress System And Autophagy Machinerymentioning
confidence: 99%
“…In previous studies, we could show that β,β-dimethylacrylshikonin ( 2 ) was the most cytotoxic compound isolated from the roots of O. paniculata and exhibited the strongest cytotoxicity toward several melanoma cell lines [ 13 , 14 ]. Ongoing studies revealed that 2 favored catabolic processes and caused generation of reactive oxygen species, loss of mitochondrial membrane potential, and the upregulation of NOXA expression [ 15 , 16 ]. Finally, this led to apoptosis, autophagy, and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%